Antibodies to in silico selected GPI-anchored Theileria parva proteins neutralize sporozoite infection in vitro - Nyagwange, James; Nene, Vishvanath M.; Mwalimu, Stephen; Henson, Sonal P.; Steinaa, Lucilla; Nzau, Benjamin M.; Tijhaar, Edwin; Pelle, Roger (Elsevier, 2018)
East Coast fever (ECF) caused by Theileria parva kills cattle in East, Central and Southern Africa leading to significant economic losses. Vaccination is used as a control strategy against ECF and is presently dependent on deliberate infection with live sporozoites and simultaneous treatment with a long-acting oxytetracycline. Although effective, this method has serious limitations; the immunity is parasite strain specific and immunized cattle can become life-long asymptomatic carriers of the parasite, posing risk for the spread of the disease. In efforts to develop a subunit vaccine, the role of antibodies in the neutralization of T. parva sporozoites infection of host cells has been investigated and a circumsporozoite protein, p67, is able to induce such neutralizing antibodies. However, the p67 protein only protects a proportion of immunized cattle against T. parva challenge and such protection might be improved by inclusion of additional parasite antigens that neutralize sporozoite infection. In an attempt to identify such antigens, we searched the re-annotated T. parva genome for genes predicted to contain GPI anchor signals, since they are likely to be located on the cell surface, and expressed fragments of six of the selected genes in E. coli. The recombinant proteins were used to raise antisera in mice. Antisera to two proteins, TpMuguga_01g00876 and TpMuguga_01g00939, neutralized sporozoite infectivity to a high degree, while antisera to two additional proteins, TpMuguga_01g00095 and TpMuguga_04g00437, exhibited moderate neutralizing capacity. We conclude that these four antigens are potential vaccine candidates, which should be evaluated further in cattle.